Indirect lmunofluorescent Antibody Test for Detecting Chlamydial Infection - AL- Kaysi, A. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A total of 243 serum samples  were tested  for the presence ofChlamydia antibodies by ind irect immunofluorescent antibody test.Ninetynine females were suffering from abortions, 64 were infertile and other 80 were  none  aborted  women.  The  incidence of  Ch lamydia  were  (15%,9.4%)   and   (3.8%)   in  abortion,   infertile   and   non   aborted   group,respecti vely.  The  results  also  showed  a difference  in  prevalence rate between the age groups. The  highest  incidence was found  in the age group  20-39  years. Levels  of  inununolobu lines (1gG,  JgM)  were also detenn i ned to identify a high positi ve titer of these chosen samples.